2020
DOI: 10.1097/bpo.0000000000001594
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Use of Growth-friendly Implants for Early-onset Scoliosis: A 10-Year Update

Abstract: Background: Growth-friendly treatment of early-onset scoliosis (EOS) has changed with the development and evolution of multiple devices. This study was designed to characterize changes in the use of growth-friendly implants for EOS from 2007 to 2017. Methods: We queried the Pediatric Spine Study Group database for patients who underwent index surgery with growth-friendly implants from July 2007 to June 2017. In 1298 patients, we assessed causes of EOS; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
2
8
0
2
Order By: Relevance
“…Our data mirrors and expands on that of Klyce et al,24 who reported on MCGR use within the PSSG from 2007 to 2017. Although use of the MCGR limits some of the issues with TGR and VEPTR, this device has higher initial implant costs and its own complication portfolio, which is similar in many ways to that of TGR and VEPTR.…”
Section: Discussionsupporting
confidence: 90%
“…Our data mirrors and expands on that of Klyce et al,24 who reported on MCGR use within the PSSG from 2007 to 2017. Although use of the MCGR limits some of the issues with TGR and VEPTR, this device has higher initial implant costs and its own complication portfolio, which is similar in many ways to that of TGR and VEPTR.…”
Section: Discussionsupporting
confidence: 90%
“…Rods are lengthened in a physician’s office using a handheld magnetic device, which rotates an actuator within the rod and causes lengthening [ 62 , 63 ]. MGRs have grown significantly in popularity since their introduction, comprising < 5% of all growing rods in 2007–2008 and increasing to 83% in 2016–2017 [ 64 ].…”
Section: Dynamic Instrumentationmentioning
confidence: 99%
“…However, the use of these technologies in recent studies has been limited to younger patient populations, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with current indications in the US limited to patients with early-onset scoliosis (<10 years of age), 32,33 and while these technologies allow fusion to be delayed until skeletal maturity is reached, a final fusion procedure is still required.…”
mentioning
confidence: 99%